2014
DOI: 10.2967/jnumed.113.123018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Recurrent Prostate Cancer After Radical Prostatectomy: Comparison of 11C-Choline PET/CT with Pelvic Multiparametric MR Imaging with Endorectal Coil

Abstract: The aim of this study was to compare 11 C-choline PET/CT with pelvic multiparametric MR imaging for detection of recurrent prostate carcinoma in patients with suspected recurrence after radical prostatectomy and to identify an optimal imaging method to restage these patients. Methods: This was a retrospective, single-institution study of 115 prostatectomy patients with suspected tumor recurrence who underwent both 11 C-choline PET/CT and multiparametric MR imaging with endorectal coil. The reference standard i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(150 citation statements)
references
References 15 publications
4
141
0
4
Order By: Relevance
“…Souvatzoglou et al found 11 C-choline uptake in the prostatic bed in 7 of 37 patients (19%) who had PSA failure after RP and were candidates for salvage radiotherapy (RT) of the prostatic fossa (6). These data were substantially confirmed by Kitajima et al, who found a sensitivity of 54% and a specificity of 92% for 11 C-choline PET/CT in the detection of local relapse in 87 patients after RP (7).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Souvatzoglou et al found 11 C-choline uptake in the prostatic bed in 7 of 37 patients (19%) who had PSA failure after RP and were candidates for salvage radiotherapy (RT) of the prostatic fossa (6). These data were substantially confirmed by Kitajima et al, who found a sensitivity of 54% and a specificity of 92% for 11 C-choline PET/CT in the detection of local relapse in 87 patients after RP (7).…”
supporting
confidence: 72%
“…Various studies have investigated the diagnostic accuracy of 11 C-choline PET/CT for detecting PCa recurrence and have reported different values for sensitivity and specificity (5,(7)(8)(9)11,12,14). These variations could be attributed to the heterogeneity of patient populations in terms of inclusion criteria (i.e., PSA level, staging, and presence or absence of androgen deprivation therapy [ADT]).…”
Section: Influence Of Psa On Rate Of Detection By 11 C-choline Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the bone scan, serum markers showed advantages in their reproducibility, non-invasiveness, and relatively low cost. Serum prostate specific antigen (PSA) level can predict the lesion range of prostate cancer; PSA and alkaline phosphatase (ALP) are important predictors for bone metastasis (Kitajima et al, 2014;Pasoglou et al, 2015); serum bone sialoprotein (BSP) levels reflect the process of bone resorption and bone cell activity; and bone resorption marker collagen type I pyridine crosslinking peptide (ICTP) indicates bone cell function and bone absorption rate that has certain diagnostic significance in bone metastases (Luna et al, 2015;Pasoglou et al, 2015). This study investigated serum PSA, ALP, BSP, and ICTP levels in prostate cancer patients and the significance of receiver operating characteristic (ROC) curve in the diagnosis of prostate cancer bone metastasis to provide the basis for early diagnosis and treatment of bone metastases.…”
Section: Introductionmentioning
confidence: 99%
“…20 Nos trabalhos publicados são referidos valores variáveis de sensibilidade, especificidade, valores preditivos positivo e negativo, e acuidade diagnóstica. Apesar da disparidade dos números, a PET/CT com FCH-F18 é, provavelmente, a técnica imagiológica com melhores resultados no estadiamento/restadiamento do CaP, quer na identificação de metástases ganglionares, 21 quer na deteção de metástases esqueléticas intra-medulares. 22 Apresenta, ainda, bons resultados na detecção de doença oculta, com uma taxa de sucesso de 74%, e na distinção entre doença localizada e sistémica.…”
unclassified